Mode of delivery and outcomes by birth weight among spontaneous and induced singleton cephalic nulliparous labors. Issue 1 (April 2015) - Walsh, Jennifer M.; Hehir, Mark P.; Robson, Michael S.; Mahony, Rhona M.
Abstract Objective To assess the effect of birth weight on mode of delivery among nulliparous women in a setting with no policy of elective induction for suspected macrosomia. Methods In an observational study, data were assessed from nulliparous women with a single cephalic pregnancy of at least 37 weeks in spontaneous (Robson group 1) and induced (Robson group 2a) labor attending a hospital in Dublin, Ireland, between January 1, 2008, and December 31, 2009. The primary outcome measure was mode of delivery. Results A total of 7528 nulliparous labors were included (4989 in group 1 and 2539 in group 2a). The cesarean section rate was 15.1% overall (n = 1139), with 411 (8.2%) in group 1, and 728 (28.7%) in group 2a. Cesarean delivery rates rose with increasing birth weight in group 1, from 119 (6.3%) of 1886 infants weighing 3000–3499 g and 160 (8.5%) of 1892 weighing 3500–3999 g, to 19 (26.8%) of 71 weighing 4500–4999 g. Rates of cesarean delivery were significantly higher in induced labor (group 2a) for each birth-weight category, ranging from 202 (25.9%) of 781 weighing 3000–3499 g and 243 (27.0%) of 899 weighing 3500–3999 g, to 38 (48.1%) of 79 weighing 4500–4999 g (P < 0.01 for all). Conclusion In a setting with standardized management of labor, birth weight remains a significant determinant of mode of delivery.